The development of tourism through"Abu-l Mu'in an-Nasafi" scientific research center (Journal of Universal Science Research, 2023)
In this article, in the years of independence based on the increasing attention to cultural heritage, including the establishment of the Abu-l Mu'in al-Nasafi scientific-research center in Kashkadarya, the goals and tasks of the center and the development of the tourism industry in the region were considered.